Childfree Marriages in Islamic Perspective: A Maqāṣid al-Sharīʿah Analysis of Spousal Choice and Reproductive Intentions (CV. Era Digital Nusantara, 2025)
The contemporary rise of intentional childfree unions has sparked scholarly debate on the compatibility of spouse-driven reproductive decisions with Islamic legal objectives. This study examines the phenomenon of childfree marriage through the theoretical lens of Maqāṣid al-Sharīʿah as articulated by al-Ṣāṭibī, focusing on the protection of progeny (ḥifẓ al-nasl) among the five foundational objectives. Employing a qualitative literature review of Indonesian and international sources, this article maps the socio-cultural factors economic considerations, career priorities, health constraints, and ethical concerns that motivate couples to forgo parenthood. It then assesses how these motivations align or conflict with the sharīʿah’s hierarchical categories of necessities (darūriyyāt), needs (ḥājiyyāt), and refinements (taḥsīniyyāt). A critical analysis of classical and contemporary Islamic juridical opinions on contraception, ‘azl (coitus interruptus), and permanent sterilization elucidates the juristic reasoning that permits or prohibits reproductive control measures. The study further explores Fatwa decisions by the Indonesian Ulema Council (MUI) from 1979 to 2012, highlighting shifts in permissibility under exigent circumstances. Findings reveal that while temporary child spacing aligns with secondary objectives (ḥājiyyāt) when safeguarding maternal health, permanent childfree choices conflict with primary objectives (darūriyyāt) unless justified by compelling necessity. The article concludes by proposing a nuanced legal framework that upholds spousal autonomy and welfare while preserving the maqāṣid’s commitment to lineage continuity. Recommendations call for dynamic fiqh responses that balance individual rights with communal interests in sustaining Muslim ummah growth.